'Random‐flight' dispersal in tropical fruit‐feeding butterflies? High mobility, long lifespans and no home ranges. (28th August 2015) - MARCHANT, NICHOLAS C.; PURWANTO, ARI; HARSANTO, FRANSISKUS A.; BOYD, NICHOLAS S.; HARRISON, MARK E.; HOULIHAN, PETER R.
Abstract : 1. Tropical fruit‐feeding Nymphalidae butterflies are widely used in research, monitoring, and conservation projects, but to date a key aspect of their behaviour – dispersal – remains poorly understood. They have anecdotally been described as 'relatively sedentary' based on movement vectors from mark‐recapture studies, but this may be inaccurate because plot‐based studies in small sampling areas often underrepresent long‐distance movements. 2. Based on data from a peat‐swamp forest in Borneo, it was found that these butterflies may be much more mobile than previously thought, as they frequently moved distances of 1–2 km between sampling plots. Median daily movements were approximately 200–250 m, and over lifespans of one or more months these movements may sum to total life‐time dispersals of several kilometres. 3. Recapture rates for long‐distance movements between sampling plots were between 28.2% and 41.6% of the re‐encounter rates that would be predicted by a random‐walk approximation/Brownian motion (without accounting for survival rates), supporting the hypothesis that it is a suitable model of dispersal in this group, although further research is needed to confirm this. 4. There was no evidence that butterflies occupied permanent home ranges, and it is suggested that a permanent home range or territorial behaviour would be maladaptive in this group. Pseudo‐replication caused by 'trap‐happy' behaviour was not found to be widespread, and some recommendations are provided regarding the treatment of recapture data in trap‐based studies. 5. These findings substantially increase the spatial parameters for future research and conservation projects in this group and are also applicable to theoretical modelling studies. An abstract for this article in Bahasa Indonesia is included in the online supporting information File S1.